2021
DOI: 10.34133/2021/9797058
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam Irradiation Induced Regulation of Surface Defects in Lead Halide Perovskite Thin Films

Abstract: Organic-inorganic hybrid perovskites (OIHPs) have been intensively studied due to their fascinating optoelectronic performance. Electron microscopy and related characterization techniques are powerful to figure out their structure-property relationships at the nanoscale. However, electron beam irradiation usually causes damage to these beam-sensitive materials and thus deteriorates the associated devices. Taking a widely used CH3NH3PbI3 film as an example, here, we carry out a comprehensive study on how electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The area of a single damaged zone is 5 × 5 µm, and the thickness is estimated to be 25–45 nm (Experimental Section). [ 52 ] The second step is the surface lattice repair of thin films in the MAPbX 3 supersaturated HX aqueous precursors solutions. In the supersaturated solutions, the Gibbs free energy ( G ) is much higher than that of MAPbX 3 solids at room temperature (25 °C); the negative G change (Δ G ) drives the growth of perovskite crystal, and the isolated PbX 6 4− octahedral cages move and rearrange to construct the destroyed areas, thus filling the vacancies on the surface of the single‐crystalline thin film.…”
Section: Resultsmentioning
confidence: 99%
“…The area of a single damaged zone is 5 × 5 µm, and the thickness is estimated to be 25–45 nm (Experimental Section). [ 52 ] The second step is the surface lattice repair of thin films in the MAPbX 3 supersaturated HX aqueous precursors solutions. In the supersaturated solutions, the Gibbs free energy ( G ) is much higher than that of MAPbX 3 solids at room temperature (25 °C); the negative G change (Δ G ) drives the growth of perovskite crystal, and the isolated PbX 6 4− octahedral cages move and rearrange to construct the destroyed areas, thus filling the vacancies on the surface of the single‐crystalline thin film.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when we conducted the irradiation at cryogenic temperature (130 K), cracks caused by the chilling shrinkage gradually vanished, in contrast to the phenomenon at room temperature (Figure e–g). Densely packed grains are expected in perovskite films, as they are beneficial to the efficiency and stability of the device. , We speculate that the e-beam-induced heating effect that accompanies lattice expansion rather than radiolysis dominates the surface evolution at 130 K. Moreover, it has been shown that e-beam irradiation can significantly degrade perovskite structures, resulting in a reduction of their PL intensity. However, our study reveals that the PL intensity of perovskites can be improved within a specific e-beam dose interval at both room and cryogenic temperature (Figure d and h, respectively). Furthermore, we performed e-beam irradiation on MAPbI 3 films at 130 K using three different accelerating voltages.…”
Section: Resultsmentioning
confidence: 67%
“…The evolutions of the Pb 4f, I 3d, and C 1s core-level spectra of MAPbI 3 films (MAPI (0,0) and MAPI (4,5) ) are shown in Figure S3a–c, respectively. The well-preserved peak intensities and peak positions suggested there was negligible e-beam radiolysis damage in our experiments, which cannot be ignored at room temperature. , Time-resolved femtosecond transient absorption spectroscopy (TAS) was used to study relaxation dynamics of MAPI (0,0) and MAPI (4,5) . As shown in Figure S3d and e, the decay of the bleach signal shows a strong dependence on the e-beam irradiation.…”
Section: Resultsmentioning
confidence: 70%
“…Generally, grain size and film density are the key factors to affect the quality of LFMH thin film, for which large grain size and compact distribution can generate a high‐quality thin film. [ 102 ] Recently, more and more researches have been reported to improve thin film quality through optimizing synthesis strategies. LFMH film can be prepared by vapor deposition or spin‐coating method.…”
Section: Preparation Methodsmentioning
confidence: 99%